B cells inhibit the antitumor immunity against an established murine fibrosarcoma - Maglioco, Andrea Florencia (2017)
Despite the classic role of B cells in favoring the immune response, an inhibitory action of B lymphocytes in tumor immunity has emerged in certain studies. In methylcolanthrene-induced murine fibrosarcoma (MCC), the loss of immunogenicity and the establishment of tolerance are paralleled by systemic immune suppression and the appearance of B+IL‑10+ cells in tumor‑draining lymph nodes. The present study aimed to assess the role of the B+IL‑10+ cell population in the immune evasion and tolerance induced by MCC through the depletion of B cells in mice at various times of tumor progression: Prior to or subsequent to tumor implantation. Tumor growth and immunological parameters were evaluated. B cell depletion prior to tumor inoculum enhanced tumor growth, initiating the onset of the tumor‑induced systemic immune response; however, an increase in the T regulatory cells (Tregs) at the tumor‑draining lymph node could account for tumor exacerbation. B cell depletion once the tumor was established resulted in decreased tumor growth and a delayed onset of tolerance. Additionally, B cell absence exacerbated T cell dependent‑tumor rejection, reduced Tregs and increased cytotoxic CD8+ T cells. In vitro analysis showed a direct effect of B cells upon T cell proliferation. In conclusion, B cell depletion exerts opposite effects when performed prior to or subsequent to tumor implantation. In this initially immunogenic tumor, B cell absence would delay the establishment of immunological tolerance probably by unmasking a pre‑existing antitumor response. The present findings elucidate the convenience of modulating B cells in the development of future and more effective immunotherapies against cancer.